Return to Havana : the decline of Cuban society under Castro - Halperin, Maurice, 1906- (Vanderbilt University Press, 1994)
"A personal account from a prominent intellectual whose writings on Cuba have become a mixture of disillusionment and fatalism. This book is based on an account of Halperin's visit in 1989, which left him less optimistic than ever about Cuba's future. He found 'the popular mood one of deep discouragement' (p. 190) and could not imagine 'any young Cuban, or even older ones, prepared to die for socialism.'"--Handbook of Latin American Studies, v. 57.